Influenza A(H3N2) Virus in Swine at Agricultural Fairs and Transmission to Humans, Michigan and Ohio, USA, 2016 - Bowman, Andrew S. (Emerg Infect Dis, 2017)
In 2016, a total of 18 human infections with influenza A(H3N2) virus occurred after exposure to influenza-infected swine at 7 agricultural fairs. Sixteen of these cases were the result of infection by a reassorted virus with increasing prevalence among US swine containing a hemagglutinin gene from 2010–11 human seasonal H3N2 strains.